Japan and South Korea’s response to the Russian Invasion of Ukraine (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
The Full-Scale Russian Invasion of Ukraine in 2022 has far-reaching consequences, not only reshaping the situation in Europe but also impacting the global landscape. This chapter aims to present and analyze the stances and actions of Japan and South Korea concerning the ongoing war in Ukraine. On one hand, both countries have strong ties with the United States and the European Union, but on the other hand, they possess their distinct interests and are geographically distant from the conflict, spanning thousands of kilometers away. The analysis covers a period of one year, from the invasion until February 2023. The chapter endeavors to address questions concerning the type of aid provided to Ukraine by Japan and South Korea, the limitations faced by the authorities in Tokyo and Seoul, and their approaches towards Russia. While both countries extend support and assistance to Ukraine in response to Russian aggression, the nature of their support is influenced by legal and political constraints.